THE IMPACT OF ESG RATINGS ON FIRM FINANCIAL PERFORMANCE AND FOREIGN INSTITUTIONAL OWNERSHIP IN INDIA: A SYSTEMATIC LITERATURE REVIEW - Nandan, Mr. Sarv Pallav Krishan; Sinku, Sumita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper offers a systematic review relationship between financial performance of the form and ESG ratings in India is underexplored particularly, considering the impact it has on foreign institutional ownership. Through incorporation of the PRISMA framework, the study identified and synthesised research articles which were relevant to the context of India and published between the timeframe of 2018 and 2024. Drawing on frameworks like Agency Theory, and Stakeholder Theory the study findings imply that ESG performance is integral to enhance firm value and attract foreign investors in India. The study further highlighted the importance of regulatory and market factors shaping ESG investment decision. The study offered future research directions and practical implications for understanding the impact of ESG rating in foreign institutional ownership in India.